Analysis of Static and Dynamic Characteristics and Lightweight Design of Titanium Alloy Frame - Zheng, Bin (Manufacturing Technology Journal, 2024)
In response to the problems of insufficient strength and stiffness, as well as large weight in traditional car frames, this article takes titanium alloy frames as the research object. Based on the analysis of static and dynamic characteristics, a lightweight design is carried out to meet the design requirements. Firstly, static analysis was conducted on the frame structure under four different working conditions using the finite element analysis method to study its stress distribution and deformation under different loads and road conditions. Study the natural frequency and vibration mode of the frame through modal analysis, providing a basis for subsequent optimization design. Through harmonic response analysis, explore the changes in the amplitude and frequency of the frame during use. On this basis, topology optimization and lightweight design are carried out on the frame structure to reduce the weight of the frame and improve its strength and stiffness. Finally, validate and compare the optimized frame to explore the feasibility and superiority of the optimization plan. The research results show that the optimized frame weight has been reduced by 13.76%, the maximum stress has been reduced by 5.19%, and the maximum deformation has been reduced by 0.37%, effectively reducing the frame mass. This provides a way of thinking about the static and dynamic characteristics analysis and topology optimization design of automotive frames.
Keywords: Titanium alloy frame; Topology optimization; Finite element analysis; Light weight design